Efficacy and safety of Janus kinase inhibitors in the treatment of psoriasis and psoriatic arthritis: An analysis of evidence from 2014 to 2022 - Jiao Wang; Tian Ma; Xiaoying Sun; Liu Liu; Seokgyeong Hong; Huijung Cha; Miao Zhang; Jiale Chen; Naixuan Lin; Bin Li; Xin Li (Heliyon)
Background: The efficacy and safety of Janus kinase (JAK) inhibitors as novel therapeutic agents for psoriasis (PSO) and psoriatic arthritis (PsA) have not yet been systematically evaluated. Methods: Randomized controlled studies (RCTs) assessing JAK inhibitors to treat PSO or PsA published before September 1, 2022, were searched in the PubMed, Embase, and Cochrane Library databases. The Psoriasis Area and Severity Index (PASI) 75 and American College of Rheumatology (ACR) 50 were established as primary outcome indicators of PSO and PsA, respectively. Adverse events (AEs) were classified according to eight systems of the human body. Results: We included 16 relevant RCTs involving 4,936 patients with psoriasis, with interventions performed using different doses of JAK inhibitors. Except in one study, all patients received a placebo or vehicle control. JAK inhibitors were administered topically in three studies and orally administered in the remaining studies. Meta-analysis revealed that oral administration of JAK inhibitors significantly improved PASI 75 in patients with PSO (risk ratio [RR] 3.29; 95 % confidence interval [CI] [2.37, 4.57]), and topical application was not effective (RR 1.45, 95 % CI [0.97, 2.15]). JAK1 and JAK3 inhibitors were more effective than JAK1/JAK 2 inhibitors for PASI 75. JAK1 inhibitors elicited high response rates in improving ACR 50 in PsA (RR 2.95, 95 % CI [1.63, 5.35]) and achieved significant results at week 16 of treatment (RR 2.95, 95 % CI [1.63, 5.35]). Oral JAK inhibitor-induced AEs were mainly related to the circulatory system (RR 3.09, 95 % CI [1.42, 6.75]). Conclusions: Oral JAK inhibitors improved clinical symptoms in patients with PSO. Tofacitinib, a JAK1 and JAK3 inhibitor, has a high response rate. Filgotinib, a JAK1 inhibitor, markedly enhanced the response rate and improved ACR scores in patients with PsA, and the best effect was achieved with 16-week oral administration.